Conflito e inovação em equipes de projetos multifuncionais - Rosa, Vanessa Marques da (2023)
This study aimed to analyze the degree of the relationship between conflict and innovation in the context of multifunctional project teams, an essential issue in the global corporate environment. The research addresses variables such as cultural intelligence, information processing and knowledge, creativity, cognitive and affective conflicts, as well as knowledge leadership, with a diverse sample of 117 professionals from countries including Brazil, Canada, Spain, Australia, India, South Africa, the Netherlands, the United Kingdom, and Spain. Using a quantitative approach, the study developed nine hypotheses, based on an extensive literature review. For data collection, validated instruments were used that allowed for an effective measurement of the constructs investigated. The analyses were performed through Structural Equation Modeling, using the Partial Least Squares method and the SmartPLS® 3.0 software. The study reveals the importance of creativity and the ability to process information for innovation, while affective conflicts harm collaboration and innovation. The research does not find a direct relationship between cognitive conflict, cultural intelligence, and knowledge leadership with innovation. The study clarifies the inter-relationship between affective conflict and innovation in teams, emphasizing the need for efficient conflict management strategies to promote organizational innovation. These insights are fundamental for leaders and managers seeking to develop innovative environments within organizations. This work represents a significant advance in understanding how internal team conflicts can influence innovation capacity.